Oral Cancer Disease among the Poor: A Sri Lankan Context - Kalpani Senevirathna; Yovanthi Anurangi Jayasinghe; Shalindu Malshan Jayawickrama; Hemantha Amarasinghe; Ruwan Duminda Jayasinghe (MDPI AG, 2023)
Oral cancer (OC) is the 16th most common cancer worldwide. In Sri Lanka, OC is the most prevalent cancer among men and the eighth among women. In most instances, OC is preceded by clinically recognizable disorders appearing on the oral mucosa, termed oral potentially malignant disorders (OPMD). The distribution of OC among low- and middle-income socioeconomic groups contributes to various factors. Poor oral health literacy, a lower quality of higher education, and the economic burden results in neglected oral health. The further economic recession has led to the formation of risk habits, such as chewing betel quid, smoking and the consumption of alcohol, among these groups to minimize stress levels. But with a lack of oral health awareness, the incidences of OC increase in this category. This review elaborates on a few cross-sectional studies conducted in various locations in Sri Lanka, discussing the low awareness of neglected oral health, the usage of tobacco in a smokeless and non-smokeless manner, consuming alcohol, and the chewing of betel nuts. This review aims to overcome the barriers in these low- and middle-income socioeconomic groups in developing nations such as Sri Lanka by creating more awareness and minimizing the incidence and diagnosis and treatment at early stages to improve the quality of life as well as longevity.